Characteristics of Women Seeking Services at a Transitional Housing Facility for Women Leaving Street-Based Sex Work: Implications for Social Service Providers. Issue 42 (1st January 2016) - Hankel, Jennifer; Heil, Misty; Dewey, Susan; Martinez, Nina
ABSTRACT: Women who decide to leave street-based sex work often struggle with addiction, trauma-related mental health consequences, and exclusion from employment and housing. To offer recommendations for social service providers, this article draws upon primary data from interviews and surveys with 87 residents at a transitional housing facility for women leave sex work to elucidate: 1) a demographic profile of the women, 2) life history patterns and circumstances that encourage women to leave street-based sex work and 3) recommendations for service providers. Results indicate the need for service providers to assist women with basic needs, strengthen referral networks, and extend trauma-informed services.